An Analysis of Ideational Metaphor in Political Text: A Study of Systemic Functional Linguistics - linda, linda; Suherman, Tatang (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
AbstractThe research entitled “An Analysis ofIdeational Metaphor in Political Text: A Study of Systemic Functional Linguistics” is aimed to find out the ways the ideational metaphor is organized in Political text. The scope in which the studyis conducted ranges from the variety of processes used in political text. The analysis is conducted in accordance with the grand theories put forwarded by Halliday, Mathiesen, and Thompson, with some supportive theoretical background from Downing and Locke, and Eggins and some theories of metaphorin general.   The result of this research shows that the types of processes found in this research almost covers all the types of processes, namely: Material, Mental, verbal, and Relational Processes. Behavioural and existential were not found under the assumption that those types have little relevant to the process of  metaphorical wording.